Implementation of Technology Based SAK EMKM - Indrianasari, Neny Tri (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
This study aims to analyze the application of Information Technology-based Accounting based on SAK EMKM. MSMEs face various obstacles or problems caused by 1) low education 2) a lack of understanding of information technology, and 3) obstacles in preparing financial reports. The Lamikro application system complies with the Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM). The presence of the Lamikro application according to the EMKM SAK is expected to help MSME players in Indonesia in preparing financial reports because the Lamikro application can make it easier for MSMEs to make financial reports whose transactions are cash in nature. Business development using accounting financial statement applications is very necessary, the goal is that users, in this case, MSME players throughout Indonesia, can monitor the financial activities of MSMEs. This type of research used in this research is descriptive research with qualitative. approach. This research concludes that the financial records of Joys Kitchen and Rezky Photocopy still use traditional or manual recording so that they do not know the recording of financial statements in accordance with EMKM's Financial Accounting Standards and are still constrained in inputting financial report transactions using Lamikro